Narrativas de trajetórias identitárias e linguageiras de migrantes - Honorato, Patrícia Rafaela de Morais (2020)
This thesis aims to raise reflections on the migration of Haitians to Brazil in contemporary times and is circumscribed especially in the narratives and phenomenon of language - process of acquisition, insertion and experience of contexts of language learning, allocation and acculturation via transmission, adversities and identity reconstructions - experienced and reported by these subjects. In the same way, the theoretical-methodological choice is purposely chosen so that the studied phenomenon, theory and methodology are inscribed as complementary and bonded, constituent and constituted by the same central element, language. French Discourse Analysis and Psychoanalysis are fundamental theoretical and methodological frameworks in structuring discussions on the migratory experience, their objective and abstract provocateurs elements and developments within the territory and the subject. Three studies were constructed to support the evoked discussion. The first chapter, a theoretical essay, had the purpose of discussing the speeches about knowledge and the concept of subject as well as the desubjectivations inscribed between the lines in these speeches. Proposes to rescue the paths of the constructions of knowledge and allocate them in the theoretical constructions about nonknowing - propositions launched by Psychoanalysis and French AD, marked by the assumption that the subject escapes the apprehensible but that it emerges in the face of the summons of the experiences. Re-presents the possibility of discussion about a subject in fact, that completely unapprehensible, that ex-ists to any formal knowledge. The subsequent two chapters consist of empirical articles, from data collected between 2016 and 2020, including individual open interviews and participant observation. The first empirical article proposes to analyze the migratory experience of Haitian women to Brazil by objective, subjective and cultural foundations. Also aims to analyse effects and consequences of the arrival and allocation in Brazil, permeating the learning of the Brazilian Portuguese language, an attempt to integrate into the work and social life of the new community, resulting in the report of subjective (im)possible displacements to be exercised or allocated, articulated through Lacan's Four Discourses theory. The second empirical article deals with a proposal for reflection on selfnarratives of Haitian migrant subjects in their individual experience of language acquisition and the effects of the new way of expressing themselves, in their contingencies and (un)bonding. The textual production of this thesis does not envisage in any way reaching the ex-isting infinity of singularities of the subjective experience of Haitian and Haitian migrants, but it modestly proposes a reflexive approach through theoretical and methodological modalities that challenge us in a perceptual rearrangement, invite us to look for what escapes the studies of the migratory phenomenon, but persists and overflows to formal knowledge - these subjects.